Effect of exogenous phytase added to small-quantity lipid-based nutrient supplements (SQ-LNS) on the fractional and total absorption of zinc from a millet-based porridge consumed with SQ-LNS in young Gambian children: a randomized controlled trial. Issue 6 (5th September 2019) - Zyba, Sarah J; Wegmüller, Rita; Woodhouse, Leslie R; Ceesay, Kabiru; Prentice, Andrew M; Brown, Kenneth H; Wessells, K Ryan
ABSTRACT: Background: Dietary phytate inhibits zinc absorption from composite meals in adults. Objective: The objective of this study was to investigate the effect of adding exogenous phytase to a small-quantity lipid-based nutrient supplement (SQ-LNS) on zinc absorption among young children. Methods: In a double-blind randomized controlled trial, intraindividual differences in fractional and total absorption of zinc (FAZ and TAZ, respectively) from a millet-based porridge containing SQ-LNS with and without phytase were measured in 30 asymptomatic children 18–23 mo of age in the Kiang West district of The Gambia. Using a crossover design, children received for 1 d each porridge test meals with 20 g SQ-LNS containing 8 mg zinc and either 1 ) exogenous phytase or 2 ) no exogenous phytase. The test meals were provided on consecutive days in randomized order. FAZ was measured using a triple stable isotope tracer ratio technique with Zn-67 and Zn-70 as oral tracers and Zn-68 as the intravenous tracer. Results: Twenty-six participants completed the study. The prevalence of stunting and wasting were 20% and 13%, respectively; no children had low plasma zinc concentrations (<65 μg/dL). Total mean ± SD dietary zinc intake from the test meals was 7.3 ± 2.2 mg (phytate:zinc molar ratio = 3.1 ± 0.3, not accounting for phytase activity). Mean FAZ increased from 8.6% ± 1.3% to 16.0% ± 1.3% when exogenous phytase was added to the SQ-LNS product ( P < 0.001). Mean TAZ from test meals containing SQ-LNS with phytase was more than double that from test meals containing SQ-LNS without phytase (1.1 ± 0.1 mg and 0.5 ± 0.1 mg, respectively; P < 0.001). Conclusions: The addition of exogenous phytase to SQ-LNS increased both FAZ and TAZ. These results suggest that phytate reduction may be an important strategy to increase zinc absorption among young children. This trial was registered at clinicaltrials.gov as NCT02668133.